William T. Avery papers - Avery, William T. (William Tecumsah), 1819-1880.
Letters from Avery chiefly to his wife during the period while he was serving in Congress containing comments on Washington, D.C., social life, the business of the House, and the 1860 Democratic conventions in Charleston and Baltimore.
Lawyer, U.S. representative from Tennessee, and Confederate Army officer.
Collection material in English.
Keywords: United States. -- Congress. -- House; Washington (D.C.) -- Social life and customs; Army officers, Confederate; Lawyers; Representatives, U.S. Congress -- Tennessee